2012
DOI: 10.1002/etc.1922
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic kinetic parameters for polyfluorinated alkyl phosphate hydrolysis by alkaline phosphatase

Abstract: The hydrolysis kinetics of three polyfluorinated alkyl phosphate monoesters (monoPAPs), differing in fluorinated chain length, were measured using bovine intestinal alkaline phosphatase to catalyze the reaction. Kinetic values were also measured for analogous hydrogenated phosphate monoesters to elucidate the effects of the fluorinated chain on the rate of enzymatic hydrolysis. Michaelis constants (Km) were obtained by a competition kinetics technique in the presence of p‐nitrophenyl phosphate (PNPP) using UV‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Low absorption efficiency of some diPAP congeners such as 8:2 diPAP (<0.1%) is noted in a rat exposure study, and the half-lives of these chemicals are as short as days (6:2 diPAP, 3.9 ± 0.7 days and 8:2 diPAP, 2.4 ± 0.2 days) . DiPAPs can also be metabolized in gut to PFCAs before being absorbed in bloodstream. , Since diPAPs were reactive, the detection of diPAPs even at low concentrations in human blood implied that humans are exposed to a high level of these chemicals in their daily lives. More importantly, diPAPs are metabolized into persistent PFCAs .…”
Section: Resultsmentioning
confidence: 99%
“…Low absorption efficiency of some diPAP congeners such as 8:2 diPAP (<0.1%) is noted in a rat exposure study, and the half-lives of these chemicals are as short as days (6:2 diPAP, 3.9 ± 0.7 days and 8:2 diPAP, 2.4 ± 0.2 days) . DiPAPs can also be metabolized in gut to PFCAs before being absorbed in bloodstream. , Since diPAPs were reactive, the detection of diPAPs even at low concentrations in human blood implied that humans are exposed to a high level of these chemicals in their daily lives. More importantly, diPAPs are metabolized into persistent PFCAs .…”
Section: Resultsmentioning
confidence: 99%
“…Perfluoroalkyl acids (PFAAs) are anthropogenic organic chemicals utilized in a wide range of commercial and industrial applications for their surface active properties and include perfluoroalkyl carboxylates (PFCAs) and perfluoroalkanesulfonates (PFSAs). The presence of PFCAs and PFSAs is well-documented, with global measurements in every environmental compartment. These substances are environmentally persistent and are products of environmental transformation of other labile polyfluoroalkyl substances. …”
Section: Introductionmentioning
confidence: 99%
“…4,5 The observation of diPAPs in human blood is an indicator that humans are exposed to fluorotelomer-based commercial materials. This warrants attention because diPAPs have been shown to be enzymatically hydrolyzed to produce the corresponding fluorotelomer alcohol (FTOH), 6 which subsequently yields perfluorinated carboxylates (PFCAs) (Figure 1). 7−9 FTOHs are building blocks in many fluorotelomer-based commercial applications, and as a result have been found as residuals in fluorotelomer-based manufactured products.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The observation of diPAPs in human blood is an indicator that humans are exposed to fluorotelomer-based commercial materials. This warrants attention because diPAPs have been shown to be enzymatically hydrolyzed to produce the corresponding fluorotelomer alcohol (FTOH), which subsequently yields perfluorinated carboxylates (PFCAs) (Figure ). FTOHs are building blocks in many fluorotelomer-based commercial applications, and as a result have been found as residuals in fluorotelomer-based manufactured products . The biotransformation of FTOHs, primarily 8:2 FTOH, has been extensively studied, as FTOHs can oxidize to produce PFCAs. Due to the production of PFCAs from FTOH transformation, current efforts are in place to remove 100% of the FTOH residuals on commercial products by 2015. , PFCAs that have carbon chain lengths ≥8 are bioaccumulative and have been observed in human sera at ng/mL concentrations. Additionally, animal studies have demonstrated that perfluorooctanoate (PFOA), the C8 PFCA congener, is associated with peroxisome proliferation, and developmental and immunological effects. , …”
Section: Introductionmentioning
confidence: 99%